2017
DOI: 10.1038/srep44244
|View full text |Cite
|
Sign up to set email alerts
|

AKT1 and AKT2 isoforms play distinct roles during breast cancer progression through the regulation of specific downstream proteins

Abstract: The purpose of this study was to elucidate the mechanisms associated with the specific effects of AKT1 and AKT2 isoforms in breast cancer progression. We modulated the abundance of specific AKT isoforms in IBH-6 and T47D human breast cancer cell lines and showed that AKT1 promoted cell proliferation, through S6 and cyclin D1 upregulation, but it inhibited cell migration and invasion through β1-integrin and focal adhesion kinase (FAK) downregulation. In contrast, AKT2 promoted cell migration and invasion throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
112
2
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(128 citation statements)
references
References 58 publications
11
112
2
3
Order By: Relevance
“…Remarkably, we found that silencing of Vav1 increased the phosphorylation level of Akt1 at Ser473, known to be required for its maximal activity (Guo et al ., ). By investigating in vitro the main events triggered by activated Akt1, we demonstrated that the downmodulation of the p‐Akt1 (Ser473) level induced by Vav1 in MDA‐MB‐231 cells correlates with their reduced proliferation rate, possibly mediated by the Akt/S6K pathway, a well‐described mechanism in breast tumor cells (Riggio et al ., ). The reduced size of xenografts derived from MDA‐MB‐231 stably overexpressing Vav1 confirmed the in vivo role of this protein as a strong suppressor of Akt1 activity in cells with a TNBC phenotype.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Remarkably, we found that silencing of Vav1 increased the phosphorylation level of Akt1 at Ser473, known to be required for its maximal activity (Guo et al ., ). By investigating in vitro the main events triggered by activated Akt1, we demonstrated that the downmodulation of the p‐Akt1 (Ser473) level induced by Vav1 in MDA‐MB‐231 cells correlates with their reduced proliferation rate, possibly mediated by the Akt/S6K pathway, a well‐described mechanism in breast tumor cells (Riggio et al ., ). The reduced size of xenografts derived from MDA‐MB‐231 stably overexpressing Vav1 confirmed the in vivo role of this protein as a strong suppressor of Akt1 activity in cells with a TNBC phenotype.…”
Section: Discussionmentioning
confidence: 97%
“…Overall, our data indicate that, in breast tumor‐derived cells with different phenotypes, the sole modulation of Vav1 is sufficient to affect the activation status of Akt1, involved in the insurgence and growth of breast tumors, but not of Akt2, mainly responsible of tumor metastasis (Dillon et al ., ; Riggio et al ., ). These data also suggest that, only in breast tumor cells with an ER‐negative phenotype, low Vav1 levels promote high expression of Akt2 that may be recruited and activated by specific environmental events.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Finally, on the cytogenetic bands encoding the Cbl receptor protein genes: TC-R (CD320) on 19p13.2, MEG (LRP2) on 2q31.1, cubilin (CUBN) on 10p13, amnionless (AMN) on 14q32.32, and ASGP-R (ASGR1 and ASGR2) on 17p13.1, are foci of gene amplification or mutations that support breast tumor progression, for example, the amplification of DNMT1 on 19p13.2 [47], PDK1 on 2q31.1 [48], CAMK1D on 10p13 [49], and AKT1 on 14q32.32 [50] and mutations of TP53 on 17p13.1 [51]. Intriguingly, with the concentration of sCD320 increasing in urine and serum during pregnancy, it suggests that the protein fragment may be a biomarker for cellular proliferation [52].…”
Section: Cbl Transport and Receptor Proteins In Breast Cancermentioning
confidence: 99%
“…AKT2 is involved in insulin-mediated regulation of glucose homeostasis. However, a number of studies on AKT2 have focused on its role in tumors and demonstrated that AKT2 is essential for tumor growth, colony formation and cancer cell proliferation, including ovarian cancer (18), breast cancer (19), and hepatocellular carcinoma (20). According to these studies, an AKT isoform has a vital role in tumor growth, colony formation and cancer cell proliferation in other lung diseases, in addition to lung tumors; however, there are contradictory results concerning its functions.…”
Section: Discussionmentioning
confidence: 99%